1980
DOI: 10.1002/eji.1830100308
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptors on rabbit lymphocytes. Identification and organ distribution of rosette‐forming cells; cocapping with surface immunoglobulin

Abstract: Fc receptor (FcR)-bearing cells were demonstrated using ox erythrocytes coated with homologous IgG-type antibodies (EA gamma) in rabbit peripheral blood leukocytes (PBL) and in various lymphoid organs. Discrimination of the rosette-forming cells (RFC) is carried out after prior ingestion of tetramethylrhodamine isothiocyanate-labeled latex particles and in transmission electron microscopic studies. Most of the nonlymphoid cells (5-10%) in PBL and spleen cell suspensions expose FcR. These nonlymphoid cells are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The high levels of proliferation induced among BM cell populations by IC were ac companied by increased proportions of FcyR+ cells. Since 80% of rabbit FcyR+ lymphocytes have been re ported to be B cells [15], the preferential induction of FcyR+ cells by 1C was consistent with the findings of Morgan and Weigle [10], who reported that IC in duced B cell proliferation and polyclonal activation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The high levels of proliferation induced among BM cell populations by IC were ac companied by increased proportions of FcyR+ cells. Since 80% of rabbit FcyR+ lymphocytes have been re ported to be B cells [15], the preferential induction of FcyR+ cells by 1C was consistent with the findings of Morgan and Weigle [10], who reported that IC in duced B cell proliferation and polyclonal activation.…”
Section: Discussionsupporting
confidence: 79%
“…Such increase in FcyR expression may have been necessary before these cells could respond to IC [10]. If B cells were the targets of IC stimulation [10], then FcyR+ cell suppression must have acted on an early stage of differentiation because B cells [15] and pre-B cells [16] would have been removed by the rosetting techniques. The inability of FcyR+ suppressor cells to block stimulation with IC might have been due to the preferential induction by IC of IgG responses [8], since BM suppressor cells have been reported to block IgM, but not IgG responses [1].…”
Section: Discussionmentioning
confidence: 99%
“…(c) Whole blood was mixed with Earle's 1% BSA medium, layered on Ficoll-Hypaque (e 1.077) and centrifuged for 30 min at 1000 x g as described by B~y u m [15]. Cell suspensions from lymphoid organs were prepared by pushing minced tissues through nylon gauze and washing the cells in cold medium [13].…”
Section: Lymphocyte Isolation Methodsmentioning
confidence: 99%
“…The F(ab'h y components of anti-Ig antisera were prepared by pepsin digestion followed by filtration over Sephadex G-150 and a Staphylococcal Protein A-Sepharose 4 B column (Pharmacia, Uppsala, Sweden) to remove residual Fc and undigested IgG. Conjugation with fluorescein isothiocyanate (FITC) or tetramethylrhodamine isiothiocyanate (TRITC) was performed as will be described [13] and gave rise to conjugates with molar fluorochrome/protein ratios of 1.8-4.5. All conjugates were centrifuged (30 min, 10000 x g), filtered through 0.45 p Millipore membranes and stored in 20 ml aliquots at -20°C.…”
Section: Fluorescent Conjugates Of F(ab')z Fragmentsmentioning
confidence: 99%